A study on the decision-making mechanism and promotion policy of urban residents’ domestic waste-classification behavior: evidence from Sichuan province - Dong, Qianyu; Yan, Rui; Xiong, Runli; Xie, Weikai; Pang, Min; Liang, Lin (Environment, development and sustainability, 2025)
The classification policy of urban domestic waste affects social welfare and sustainable development. Urban residents’ behaviors are crucial to the policy. This paper proposes a decision model of urban residents’ domestic waste-classification behaviors. Using the NetLogo simulation platform, a “policy-behavior” simulation model was built to explore the impacts of different policy tools on residents’ waste-classification behaviors. The results show that community support, perceived utility, government mobilization and environmental cognition are important factors explaining residents’ waste-classification behaviors. Informative, command-and-control, economic-incentive policy tools can significantly promote residents’ waste classification. Moreover, the incentive effect of informative, command-and-control policy tools, increases as the intensity of policy intervention increases. However, the incentive effect of economic-incentive policy tools increases and then decreases.